Critical-Multimodal Discourse Analysis on The Encyclopedia 4D Series Textbook for Early Childhood Education Students - Wahyuni, Irma; Ruhendi Syaifullah, Aceng; Gunawan, Wawan (Universitas Cokroaminoto Palopo, 2022)
This study aims to reveal the use of textual and visual-digital language in textbook used as learning materials for children at the Early Childhood Education (PAUD) level in Bogor. The book becoming the subject of the research is the 4D Encyclopedia Series for Children, Dinosaurs series. The data sourced from selection results related to text, and visual-digital images that are adapted to the language level of children at the Early Childhood Education (PAUD) level. The researcher will use a critical multimodal discourse analysis and children language development theory to find out the level of compatibility between the discursive level in discourses presented in the book in textual and digital (audio-visual) form with Android based artificial intelligence technology. Interview with the textbook users was conducted as well to triangulate data of the research findings. The results of this study are expected to be a source of information for linguistic and education researchers in the future in exploring more about textual, visual, and digital language editorials in textbooks that are used as a basis for teacher reference in teaching. In addition, the results of this study are also expected to provide insightful perspectives for writers and book designers in creating works that are appropriate to the level of students.